TEACHER PERCEPTIONS OF KURIKULUM MERDEKA IMPLEMENTATION IN SCIENCE LEARNING - Rizalmi, Rahma; Putri, Rahmah Evita (Department of Science Education, 2025)
This research purpose to know the teacher's perception of Kurikulum Merdeka implementation in learning science. Kurikulum Merdeka was implemented because of an educational gap after the Covid-19 pandemic occurred in Indonesia. The implementation of Kurikulum Merdeka is divided into Kurikulum Merdeka Mandiri Belajar, Berbagi, and Berubah. The sample of this research were schools that implemented Kurikulum Merdeka Mandiri Berbagi and Berubah. Schools implementing Kurikulum Merdeka Mandiri Berbagi are SMPN 7 Padang, SMPN 10 Padang, SMPN 11 Padang, as well as schools implementing Kurikulum Merdeka Mandiri Berubah are SMPN 3 Padang, SMPN 25 Padang, and SMPN 38 Padang. The research was a researchs in qualitative descriptive which is conducted by distributing questionnaires to science teachers who apply Kurikulum Merdeka in learning. The questionnaire used consisted of 40 statement items and 6 questions related to Kurikulum Merdeka in science learning. The results of the whole questionnaire show that 90% of science teachers understand and agree with the aspects of Learning Outcomes in the Kurikulum Merdeka 90% on Assessment statement points, 89% on Learning Model points, 76% on Lesson Time Allocation statement points, and 89% at the point of Projek Penguatan Profil Pelajar Pancasila statement. We got the conclussion that the implementation teacher's perception of Kurikulum Merdeka in learning of science is positive.